Nasal Cytological Changes as Late Effects of Radiotherapy for Nasopharyngeal Cancer. Issue 2 (March 2015) - Riva, Giuseppe; Boita, Monica; Ravera, Mattia; Moretto, Francesco; Badellino, Serena; Rampino, Monica; Ricardi, Umberto; Pecorari, Giancarlo; Garzaro, Massimiliano
Background: Radiation therapy is a cornerstone in nasopharyngeal cancer treatment. However, it can induce acute and long-term adverse effects, such as acute mucositis and late submucosal fibrosis. Late toxicities could not only affect submucosa but also mucosal cells, determining long-term cytological changes. Objective: Evaluation of delayed nasal cytological alterations in patients who underwent radiation therapy for nasopharyngeal carcinoma (NPC). Methods: In this case-control study, we analyzed 30 healthy subjects and 30 patients treated with chemotherapy and radiotherapy for NPC between 2003 and 2011, with a median follow-up of 59 months. All subjects underwent symptoms anamnestic evaluation (rhinorrea, nasal obstruction), endoscopic fiber optic nasal examination, skin-prick tests, and nasal scraping for cytological exam. Results: A higher percentage of rhinorrhea, nasal obstruction, mucosal hyperemia, and presence of nasopharyngeal secretions at fiber optic endoscopic exam was found in radiated subjects (p < 0.05). Nasal cytology analysis demonstrated a higher percentage of neutrophilic inflammation and squamous cell metaplasia and mucous cell metaplasia in treated patients (p < 0.05). No cytological atypia was seen. No statistically significant correlation between nasal cytological changes and objective findings, patients' age, tobacco smoking, and gastroesophageal reflux has been found in the radiotherapy group (p > 0.05). Conclusion: Radiation therapy induces late nasal mucosal changes, which may be related to clinical consequences, such as abundant mucus production and its consequent endonasal stagnation. In the future, detailed knowledge of cytological changes in patients' nasal mucosa could represent a key prerequisite for the choice of effective interventions for late radiation-induced rhinitis.